Universal health coverage in Turkey: enhancement of equity - Atun, Rıfat; Aydın, Sabahattin; Chakraborty, Sarbani; Sümer, Safir; Aran, Meltem; Gürol, İpek; Nazlıoğlu, Serpil; Özgülcü, Senay; Aydoğan, Ülger; Ayar, Banu; Dilmen, Uğur; Akdağ, Recep (Elsevier Science Inc, 2013)
Turkey has successfully introduced health system changes and provided its citizens with the right to health to achieve universal health coverage, which helped to address inequities in financing, health service access, and health outcomes. We trace the trajectory of health system reforms in Turkey, with a particular emphasis on 2003-13, which coincides with the Health Transformation Program (HTP). The HTP rapidly expanded health insurance coverage and access to health-care services for all citizens, especially the poorest population groups, to achieve universal health coverage. We analyse the contextual drivers that shaped the transformations in the health system, explore the design and implementation of the HTP, identify the factors that enabled its success, and investigate its effects. Our findings suggest that the HTP was instrumental in achieving universal health coverage to enhance equity substantially, and led to quantifiable and beneficial effects on all health system goals, with an improved level and distribution of health, greater fairness in financing with better financial protection, and notably increased user satisfaction. After the HTP, five health insurance schemes were consolidated to create a unified General Health Insurance scheme with harmonised and expanded benefits. Insurance coverage for the poorest population groups in Turkey increased from 2.4 million people in 2003, to 10.2 million in 2011. Health service access increased across the country-in particular, access and use of key maternal and child health services improved to help to greatly reduce the maternal mortality ratio, and under-5, infant, and neonatal mortality, especially in socioeconomically disadvantaged groups. Several factors helped to achieve universal health coverage and improve outcomes. These factors include economic growth, political stability, a comprehensive transformation strategy led by a transformation team, rapid policy translation, flexible implementation with continuous learning, and simultaneous improvements in the health system, on both the demand side (increased health insurance coverage, expanded benefits, and reduced cost-sharing) and the supply side (expansion of infrastructure, health human resources, and health services).
WOS: 000321347000030
PubMed ID: 23810020
Keywords: Universal Health; Coverage; Enhancement of Equity